SASTRA PROFETIK KUNTOWIJOYO - Aminudin Rifai (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Prophetic literature is, basically, a work of transcendental and mystical spirit because it comes from the deific values. In additions, it tends to change the course of the civilization to a better route because of its messianic spirit. Kuntowijoyo (1943--2005) is one of the prophetic poets with his touch on blending the social themes with historical activism in his works. The balance between social and spiritual world; between deific saturation and problems faced by the society; between the life before and after death, between religious and historical experience are depicted gracefully in his works. The propheticism in Kuntowijoyo works could be traced by using Riffatere’s semiotics.